Health‐care utilization for sinusitis after pneumococcal vaccination in patients with low antibody titers. Issue 8 (10th January 2022) - Bareiss, Anna K.; Kattar, Nrusheel; Tivis, Rick; Unis, Graham; Do, Triet; Montelibano, Lawrence; Price‐Haywood, Eboni G.; McCoul, Edward
Abstract: Background: Pneumococcal antibody deficiency has been the subject of limited study in chronic rhinosinusitis (CRS) and has not been studied in recurrent acute rhinosinusitis (RARS). The 23‐valent pneumococcal polysaccharide vaccine (PPSV23) is considered for patients with nonprotective Streptococcus pneumoniae titers. We hypothesized that both RARS and CRS patients with deficient S pneumoniae titers and subsequent PPSV23 vaccination would have reduced health‐care encounters for sinusitis and fewer prescriptions for antibiotics or steroids. Methods: A retrospective cohort study was performed of patient encounters between January 2011 and December 2019. All patients included were ≥18 and ≤65 years old with a diagnosis of CRS or RARS and pneumococcal titer data. Patients with immunodeficiency and comorbid conditions requiring PPSV23 vaccination before 65 years of age were excluded. Results: A total of 938 patients were included in the study. Nonprotective antibody titers were present in 75.8% of CRS and 74.8% of RARS patients. A total of 306 patients with deficient antibody titers received the PPSV23 vaccine. Eighty‐nine percent of CRS and 90.1% of RARS patients had protective responses. Among the 217 patients with continuous data from 2 years before through 2 years after PPSV23 vaccination, a decrease in the number of encounter diagnoses of CRS ( p  < 0.0001) and RARS ( p  = 0.0006) was observed. Decreases in the frequency of antibiotic ( p  = 0.002) and corticosteroid ( p  = 0.04) prescriptions were also appreciated. Conclusion: Most patients with CRS and RARS have nonprotective antibody titers. PPSV23 administration significantly decreases health‐care utilization.